Ultimate Intrinsic SNR Depends on B 0 Orientation - Yuting Wang; Markus W. May; Marcel Gratz; Mark E. Ladd; Stephan Orzada (Magnetic Resonance in Medicine, 2026)
ABSTRACT Purpose This work aims to investigate the effect of orientation on the uiSNR in MRI. Methods Electromagnetic simulations were performed on both realistic body models and simplified geometric models. Comparisons between (1) opposite directions along the head‐foot (HF) axis, corresponding to head‐first and feet‐first patient orientations, at various field strengths, and (2) along the HF, anterior–posterior (AP), and left–right (LR) directions at 0.55 T, corresponding to closed‐bore (HF) and open (AP/LR) MR systems. The voxel‐wise ratio of uiSNR between different orientations was calculated to characterize spatial variations throughout the models. Results For closed‐bore MRI systems, flipping the patient orientation results in a spatial redistribution of uiSNR, and the magnitude of this redistribution increases with field strength. At 0.55 T, open MR systems with either AP‐ or LR‐oriented yield higher uiSNR than closed‐bore systems in the center of cylindrical‐shaped structures. In realistic body models, LR‐oriented yields higher uiSNR than AP‐oriented in most regions at 0.55 T, with both orientations outperforming HF‐oriented in the center of the body. Conclusion The uiSNR distribution varies with orientation in realistic body models. At around 0.55 T, the flexibility in orientation enabled by different magnet configurations may serve as an additional degree of freedom for improving imaging performance, as uiSNR is strongly influenced by the orientation of the main field.